The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/jor.24114
|View full text |Cite
|
Sign up to set email alerts
|

Notochordal cell matrix: An inhibitor of neurite and blood vessel growth?

Abstract: Blood vessel and neurite ingrowth into the degenerating intervertebral disc (IVD) are related to pain. In reported studies, notochordal cell (NC)-conditioned medium (NCCM) induced a regenerative response of nucleus pulposus (NP) cells, but also inhibition of neurite and vessel formation. NC matrix (NCM) derived from NC-rich NP tissue, induced even stronger anabolic effects than NCCM. Thus, the aim was to investigate whether NCM has similar anti-neurogenic and -angiogenic properties as NCCM. NCM and NCCM where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…The AF and EP are natural barriers resistant to vascular invasion due to intrinsic angiogenic inhibitors. IVD degeneration is often marked by blood vessel ingrowth, infiltration of inflammatory cells, and increased cell apoptosis (de Vries, van Doeselaar, Meij, Tryfonidou, & Ito, 2018;Freemont et al, 1997;McCann & Séguin, 2016;Phillips, Jordan-Mahy, Nicklin, & Le Maitre, 2013). For this reason, we then focused our investigation on the OAF zone in 6-month-old mice in order to reveal if Tnmd contributes to the maintenance of avascularity.…”
Section: Increased Angiogenesis Macrophages Infiltration and Apopmentioning
confidence: 99%
See 1 more Smart Citation
“…The AF and EP are natural barriers resistant to vascular invasion due to intrinsic angiogenic inhibitors. IVD degeneration is often marked by blood vessel ingrowth, infiltration of inflammatory cells, and increased cell apoptosis (de Vries, van Doeselaar, Meij, Tryfonidou, & Ito, 2018;Freemont et al, 1997;McCann & Séguin, 2016;Phillips, Jordan-Mahy, Nicklin, & Le Maitre, 2013). For this reason, we then focused our investigation on the OAF zone in 6-month-old mice in order to reveal if Tnmd contributes to the maintenance of avascularity.…”
Section: Increased Angiogenesis Macrophages Infiltration and Apopmentioning
confidence: 99%
“…The IVD is the largest avascular tissue in the body and has poor self-healing potential (Huang, Urban, & Luk, 2014). Under pathological conditions, the IVDs express pro-angiogenic factors leading to neovascularization (Cornejo, Cho, Giannarelli, Iatridis, & Purmessur, 2015;de Vries, van Doeselaar, Meij, Tryfonidou, & Ito, 2018;Freemont et al, 1997;Purmessur, Freemont, & Hoyland, 2008). However, the impact of anti-angiogenic factors in the maintenance of IVD avascularity remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“… 3 We further elucidate the immune privilege of the disc, which is established by physical and molecular barriers, such as blood-NP barrier (BNB) and FasL. 4 Although the role of NCs or the NC-derived matrix in angiogenesis remains controversial, 20 studies have shown that NC-derived factors can inhibit angiogenic processes, indicating their potential role in inhibiting vascular in-growth treatment. 9 With the use of mass spectrometry, Matta et al.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, NCM's anabolic effect on adult human NPCs was stronger compared with NCCM derived from the same porcine spines. In another in vitro study, however, 2 mg/ml NCM did not exert any anti-angiogenic and antineurogenic effects (de Vries et al, 2018b). Based on the overall promising anabolic in vitro benefits, the effect of 10 mg/ml NCM (concentration based on the dose-finding invitro pilot on canine NPCs) was tested in vivo on mildly (spontaneously) and moderately (induced) degenerated chondrodystrophic canine IVDs (Bach et al, 2018).…”
Section: Notochordal Cell-derived Ecm and Decellularized Np Tissuementioning
confidence: 99%